The Geotourism Students’ Scientific Club and 18 years of its activity at AGH University of Science and Technology - Bolek, Szymon; Szreter, Anna; Rożek, Agata; Gałka, Elżbieta (Geotourism/Geoturystyka, 2023)
The Geotourism Students’ Scientific Club (GSSC) is operating at the Department of General Geology and Geotourism of AGH University of Science and Technology (AGH UST), bringing together young enthusiasts of Earth sciences, at the Faculty of Geology, Geophysics and Environmental Protection. It has been operating continuously since 2003. The primary objective of the GSSC is to arouse interest in scientific work in the field of Earth sciences, as well as to popularise geotourism in the student community. The article reviews the most important achievements, events and activities documenting the long-term accomplishments of the GSSC. The greatest successes of the GSSC include the implementation of five rector’s grants and active participation in national and international scientific conferences. It is worth noting, that the GSSC organises its own “Geotourism” conference session as a part of the Conference of Student Special Interest Groups of the Mining Division. The members of the GSSC promote geology and geodiversity, explaining it in a manner which is comprehensible to an average person. Over the last dozen or so years, they have undertaken various activities, and some of them have become a tradition. Themed evenings and meetings with experts “That’s how it’s done!” attract a large audience from the university and beyond. Annual domestic and foreign educational and sightseeing trips, culminating in a trip to Iceland in 2022, have become an integral part of the GSSC activities.